Understanding the contribution of integrating spiritual intelligence into academic leadership development practice in higher education institutions Malaysia - Ramachandaran, Sharmila Devi; Ahmad, Shamsuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The study is intended to explore the contributions of integrating spiritual intelligence into leadership development practice in higher educational institutions from the perspective of academic leadership. This will lead to the development of more holistic leaders well-appointed to face with the challenges in 21st century. As such the study will be accomplished through the investigation of the lived experience of academic leaders in higher education institutions who have number of experience with the higher educational structures and policies and also vast knowledge in the field of spirituality and leadership. Qualitative interview will be conducted with academic Deans working in public universities in order to explore the contributions of integrating spiritual intelligence into their field. The interviews will be intended to focus on how the interviewers conceptualize spiritual intelligence and how it is being infused in higher educational environment. Interview questions will be prompted in order to know the interviewee’s personal experience based on their influence and involvement with spiritual intelligence practice into their professional and academic work.